1995
DOI: 10.1029/94ja03147
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and case studies of radio emissions observed near 2ƒce and 3ƒce in the auroral zone

Abstract: Receivers located at Two Rivers, Alaska (64.9øN, 146.9øW), and Circle Hot Springs, Alaska (65.5øN, 144.7øW), have been used to monitor the spectrum between 0.05-4.8 MHz for extended periods. Seasonal and diurnal effects of auroral roar, a weak narrow band radio emission near 2 and 3 times the ionospheric electron cyclotron frequency (f•), have been determined. Many individual auroral roar events correlate with magnetic activity, and superposed epoch analysis using planetary K indices shows a correlation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 22 publications
6
43
0
Order By: Relevance
“…One question that remains to be answered is why the third-harmonic source is statistically at higher altitudes than the second-harmonic source over many auroral roar events [Weatherwax et al, 1995] …”
Section: Coalescence Of Z Mode Wavesmentioning
confidence: 99%
“…One question that remains to be answered is why the third-harmonic source is statistically at higher altitudes than the second-harmonic source over many auroral roar events [Weatherwax et al, 1995] …”
Section: Coalescence Of Z Mode Wavesmentioning
confidence: 99%
“…To clarify the frequency spectra and occurrence character of the auroral radio emissions, it is necessary to take into account the nature of radio wave absorption in the ionosphere, as pointed out by Weatherwax et al (1995). This is because occurrence of the auroral radio emissions observed on the ground is certainly controlled by the collisional damping effect in the D and E regions of the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several researchers have suggested that auroral roar may be generated in the X-mode by the cyclotron maser mechanism operating at F-region altitudes [Weatherwax et al, 1995;Yoon et al, 1996]. This mechanism predicts that auroral roar should be right elliptically polarized.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism predicts that auroral roar should be right elliptically polarized. Another possible mechanism of auroral roar involves the conversion of upper hybrid waves to electromagnetic waves [Gough and Urban, 1983;Weatherwax et al, 1995]. This mechanism predicts either left-elliptical polarization (LP) or right-elliptical polarization (RP), depending on the mode conversion process.…”
Section: Introductionmentioning
confidence: 99%